Pengaruh Kualitas Produk, Kualitas Layanan, Harga Terhadap Minat Beli Ulang Melalui Keputusan Pembelian Produk Thrifting Store Swoosh - Muhammad Astrickosyah Daffa Pratama; Ana Noor Andriana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The price offered is also not far from the price of new clothes but people's interest in buying is very high. This study aims to examine the impact of service quality, product quality, and price on purchasing decisions through repurchase intention to ensure the long-term sustainability of Thrifting Swoosh stores. This study applies a type of descriptive statistical quantitative approach. The number of samples is 100 respondents using the Lameshow formula method. Primary data comes from filling out questionnaires, and secondary data is obtained through documents or other individuals. The researcher analyzed the data using the Inferential Analysis Test of the Outer and Inner models, then carried out a Hypothesis Test using the t-test statistic. The results of this study, H1 stated that the product quality variable did not have a significant effect on purchasing decisions. H2 stated that the service quality variable has no significant effect on purchasing decisions. H3 stated that the price variable has a significant effect on purchasing decisions. H4 can be stated that the purchase decision variable has no effect on repurchase intention. It can be concluded that product quality has no significant effect on purchasing decisions. Service quality and price have no significant effect on consumer buying interest at Thrifting Swoosh stores.